Scotland: a changing prescription for pharmacy: How has pharmacy changed in Scotland's community and GP practice?. Issue 5 (3rd September 2017) - Power, Ailsa
Abstract: Within primary care in Scotland, the community pharmacist is considered the first port of call for advice on minor ailments and public health issues, and providing care for people with long-term conditions. This leading article explores the educational pathway underpinning the training of these pharmacists and pharmacists working in GP practices, as they move from undergraduate through Foundation to undertake significant new patient-focused clinical roles. NHS Education for Scotland (NES) are working with these pharmacists to support these developments. In Scotland pharmacists and their teams are now very much part of the primary care team providing high quality pharmaceutical care to patients on the high street and in GP practices.